身体障害を有する精神分裂病（統合失調症）患者に対する臨床症状評価表の作成 - 仙波 浩幸; 今村 陽子; 緒方 典子; 関根 正幸; 菊地 善行; 春日 武彦; 沼尾 茲夫 (理学療法学, 2002)
The purpose of this study was to develop a clinical findings assessment table for physically disabled schizophrenic patients from the viewpoint of physical therapists, which enables the physical therapists to evaluate the psychosis easily and accurately. The subjects were physically disabled schizophrenic patients undergoing physical therapy at Tokyo Metropolitan Matsuzawa Hospital. There were a total of 129 patients, consisting of 58 males (49.8 ± 13.4 years old, mean ± SD), and 71 females (52.7 ± 15.9 years old). We developed an original psychosis scale consisting of 38 items rated on a four-point scale. The model was prepared by exploratory factor analysis of 11 items, after confirming their content validity. It was improved using the modification index obtained by comfirmatory factor analysis (structural equation modeling). As a result, a second-order latent variable model consisting of eight items was adopted. We believe that the use of this clinical findings assessment table, which consists of eight items, is beneficial for evaluation of the severity of psychosis in physically disabled schizophrenic patients from the viewpoint of physical therapists. 本研究は，身体障害を有する精神分裂病（統合失調症）患者を対象に，理学療法士が容易に，しかも正確に臨床症状を把握し評価できる臨床症状評価表の開発を目的として試作の精神症状評価尺度の妥当性を求めた。東京都立松沢病院において，身体障害により，理学療法を実施した精神分裂病（統合失調症）患者，男性58名49.8 ± 13.4歳，女性71名52.7 ± 15.9歳，合計129名を対象とした。38項目4件法からなる精神症状評価尺度を試作し，探索的因子分析により内容妥当性を確認したのち，11項目を使用して3因子からなる当初モデルを作成した。確認的因子分析（構造方程式モデリング）を用いて，修正指標，適合度指標の値よりモデルを改良したところ，8項目2次3因子モデルが最適であった。理学療法士の視点から当該患者の臨床症状を評価するには，8項目から構成する臨床症状評価表の使用が有益である。